Assessing the Impact of Early Learning Programs in Africa. Issue 158 (15th December 2017) - Gove, Amber; Brunette, Tracy; Bulat, Jennae; Carrol, Bidemi; Henny, Catherine; Macon, Wykia; Nderu, Evangeline; Sitabkhan, Yasmin
Abstract: We present results from early learning programs in six African countries: Ethiopia, Kenya, Liberia, Malawi, Tanzania, and Uganda. In partnership with ministries of education, RTI International has worked within government systems to support the design and deployment of locally contextualized materials, training, and assessment tools, with the goal of improving outcomes for early learners in primary schools, and in Kenya and Tanzania preprimary as well. Here we report on the experience and evidence of impact from specific programs in each country, including summary assessment results when available. In several countries with completed impact evaluations, there are significant and important learning gains of between 0.2 and 2.57 SD in effect size; in one case the percentage of students reaching grade‐level reading proficiency increased from 12% to 47%. In the context of increased urgency surrounding what UNESCO has called a "global learning crisis, " these experiences provide useful lessons for policymakers and practitioners alike.